Electrochemical behavior of two and one electron redox systems adsorbed on to micro- and mesoporous silicate materials: Influence of the channels and the cationic environment of the host materials - Kumar, K Senthil (ELSEVIER SCIENCE SA, 2021)
10.1016/j.matchemphys.2009.06.008